Clinical characteristics, factors associated with urinary tract infection and outcome in acutely admitted patients with infection; an exploratory cross-sectional cohort study - Mathias Amdi Hertz; Helene Skjøt-Arkil; Anne Heltborg; Morten Hjarnø Lorentzen; Mariana Bichuette Cartuliares; Flemming S. Rosenvinge; Stig Lønberg Nielsen; Christian Backer Mogensen; Isik Somuncu Johansen (Heliyon, 2024)
Background: Urinary tract infections (UTIs) remain a leading infectious disease cause of admission to the emergency department (ED) and antibiotic prescription. Heterogeneity of disease presentation challenges early diagnostics, leading to improper antibiotic prescription and delayed diagnosis. Prior studies have relied on positive urine cultures for diagnosis, but its performance suffers from false positives and false negatives. This study aimed to identify factors associated with UTIs and describe patient characteristics and outcomes while not using positive urine culture as an obligatory part of diagnosis. Methods: Adult patients admitted to the ED suspected of infection were prospectively included in an exploratory cross-sectional cohort study. An expert panel retrospectively determined the final diagnosis. Factors associated with a UTI were identified using univariate and multivariate logistic regression analysis, outcomes were evaluated with adjusted Cox regression analysis, and length of stay was compared with a zero-inflated negative binomial logistic regression model. Results: Of 966 patients who were enrolled, 200 were diagnosed with a UTI by the expert panel. We found a significant association between a UTI diagnosis and the typical UTI symptoms: dysuria (OR 7.8), change of urine appearance (OR 3.9), suprapubic or flank pain (OR 3.7), and increased urinary frequency (OR 3.2). Urinary dipstick analysis for white blood cells (WBCs) (OR 6.0–24.0), nitrite (OR 4.7), and blood (OR 3.6–12.0) was also significantly associated. Subgroup analysis of urinary dipstick analysis of men and women still showed significance in both groups. No significant difference in outcome or length of stay was found. Conclusion: Typical UTI symptoms are associated with a UTI diagnosis, which underlines the importance of exploring a patient's medical history. Urinary dipstick analysis for WBC, nitrite, and blood is also strongly associated and should be considered when evaluating patients admitted to the ED with suspicion of infection.